Pelatihan Guru Sains STEM Berbasis Robotika Sederhana: Mengembangkan Keterampilan Guru dalam Memproduksi Media Mereka Sendiri: Simple Robotics-Based STEM Science Teacher Training: Developing Teachers' Skills to Produce Their Own Media - Zulirfan Zulirfan; M. Rahmad; Yennita Yennita; Sania Kartika; Noval Kurniawan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
This community service program aims to improve science teachers' competence in understanding, assembling, and implementing simple robotic STEM Kits as project-based learning media. Activities include socializing STEM concepts and computational thinking, and training in assembling four types of automatic kits (automatic lights, automatic bridges, automatic roofs, and automatic doors). Evaluation was conducted through self-assessment questionnaires and observations of teacher activities during the workshop. The results of the activity showed a significant increase in mastery of STEM concepts, understanding of STEM Robotic tools, as well as technical skills in assembling components and operating simple carpentry tools. Most teachers were able to produce STEM media independently. Observations also showed high participation, collaborative skills, and self-confidence of participants in testing and presenting the resulting media. This program has a real impact on teacher empowerment in developing creative, innovative, and contextual science learning, and encourages the formation of the STEM MGMP community as a sustainable effort. This community service contributes to improving the quality of learning and strengthening 21st-century skills in teachers and students.